O desenho animado e o encanto do herói na TV - SANTOS FILHO, Alexandre Silva dos (Universidade Federal do Pará, 2020)
Playing with animated cartoons is quite revealing. They allow the child to play a role in the relationship and interaction process, affecting thus the ludic meaning. The aim is to reflect on the role of the child’s graphic representation as the mediating factor in ludic behaviour. Therefore, this paper also discusses the meaning of the graphic toy in the lives of children, especially when influenced by hero characters from animated cartoons. It also attempts to bring important concepts together, such as: liminal and liminoid, which characterise the ludic behaviour between art and child’s play; ludicity as an element of consequential nature; entertainment – sensitive and free; and imagination mechanisms. This reflection is based on the image references of animated cartoon series broadcast on Brazilian television. Finally, it will be said that playing with graphic forms of hero characters promotes relationship capacity and interaction with other children